1999
DOI: 10.1046/j.1365-4362.1999.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Airborne’ contact dermatitis due to Leica immersion oil

Abstract: Although phenols and ether handled by the laboratory technicians and an epoxy mastic applied during floor repair were initially suspected, an immersion oil used in light microscopy proved to be the real cause of the dermatitis. To our knowledge, these are the first reported cases due to this type of contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Multiple chemical exposures at very low concentrations are commonly present in the workplace and usually show positive reactions in the patient's skin patch test as reported in this study. Several studies have also reported that airborne contact is an important exposure route for ACD in addition to direct dermal contact [10][11][12][13]18) . We have falsified the airborne route as a possible exposure pathway by showing no allergic chemicals existing in the patient's workplace from our air monitoring results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple chemical exposures at very low concentrations are commonly present in the workplace and usually show positive reactions in the patient's skin patch test as reported in this study. Several studies have also reported that airborne contact is an important exposure route for ACD in addition to direct dermal contact [10][11][12][13]18) . We have falsified the airborne route as a possible exposure pathway by showing no allergic chemicals existing in the patient's workplace from our air monitoring results.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational dermatitis occurred mainly in construction, electronics and painting industries [1][2][3][4][5][6] in previous studies but was not reported in the automobile industry before. The cases of allergic contact dermatitis (ACD) in these studies were mainly caused by exposures to epoxy resin [1][2][3][4][5] and related compounds [6][7][8][9] through direct dermal contact, but some studies reported that airborne chemical exposure could also cause ACD [10][11][12][13] . Allergic dermal symptoms were related to qualitative exposures to chemicals in these studies [1][2][3][4][5][6][7][8][9][10][11][12][13] .…”
mentioning
confidence: 99%
“…A Leica ® immersion oil containing epoxy resins (Table 1) caused a worldwide epidemic of allergic contact dermatitis in the late 1990s (1–11). In many clinics, the patients’ own immersion oil was tested as is, which carried the risk of active sensitization.…”
Section: The Content Of the Leica® Immersion Oil According To The Matmentioning
confidence: 99%